BEHAVIOR OF LIGHT-GAUGE STEEL SHORT COLUMNS FILLED WITH NORMAL AND LIGHTWEIGHT AGGREGATE CONCRETE UNDER CONCENTRIC AXIAL LOADING - AL-Zubaidi, Ibrahim; Abdel-Jaber, Mu’tasim; Hunaiti, Yasser; El-Nimri, Rola (Journal of Applied Engineering Science, 2022)
This study aims to investigate experimentally and numerically the behavior of light-gauge steel tubes filled with normal and lightweight concrete under axial loading. A total of thirty-five specimens, including thirty-two composite columns, two bare steel columns, and one normal-weight plain concrete column, were considered. The main variables in the tests were the concrete infill type (normal-weight and lightweight), the column’s length (1, 1.25, 1.5, 1.75-m), the steel tube thickness (2 and 2.4-mm), and the cross-section (100×100 and 150×150-mm). In addition, theoretical capacities were computed according to Eurocode 4, and a finite element analysis was conducted using ABAQUS software. The results showed that the behavior of lightweight filled steel tubes was similar to the normal weight filled tubes during the test; however, their capacities were lower compared to the normal weight filled tubes by a range of (1%-20%). Yet, lightweight filled steel tubes can achieve high axial loads. In addition, the axial capacity of all composite columns decreased with the increase of the column’s height and increased with the increase of both the cross-section and the steel thickness. Current code specifications of EC4 and the numerical results obtained from ABAQUS overestimated the capacities of the composite concrete-filled tubes by 3% and 14%, respectively; however, the EC4 was found to present close estimations to the experimental results.
Keywords: light-gauge steel, lightweight concrete, composite action, finite element analysis